1999
DOI: 10.1021/es990510x
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Immobilization and Magnetite Formation via Ferric Oxide Reduction by Shewanella putrefaciens 200

Abstract: Long-term batch experiments in an artificial groundwater medium indicated that microbial reduction of synthetic, high-surface-area goethite and lepidocrocite by Shewanella putrefaciens 200 can act to immobilize surface-associated zinc into a new mineral phase that is not soluble in 0.5 M HCl. While Zn was incorporated in siderite grains in experiments with goethite, additional Zn immobilization may result from incorporation into as yet unidentified biogenic minerals or into a more crystalline goethite. Experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
96
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 121 publications
(109 citation statements)
references
References 55 publications
12
96
1
Order By: Relevance
“…(14). Cells were subsequently harvested by centrifugation and resuspended to a target optical density (A 600 , ϳ1.2) in lowionic-strength, artificial groundwater medium (AGW) (12).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…(14). Cells were subsequently harvested by centrifugation and resuspended to a target optical density (A 600 , ϳ1.2) in lowionic-strength, artificial groundwater medium (AGW) (12).…”
Section: Methodsmentioning
confidence: 99%
“…Enrichment of nitrate-reducing cultures was done with a sulfate-free AGW medium with 10 mM lactate as the electron donor and 2.5 mM nitrate as the electron acceptor. The sulfate-free medium was created by substituting chloride salts for sulfate salts in the AGW medium previously described (12). To establish enrichments, sterile sulfate-free AGW medium was degassed with nitrogen and dispensed (50 ml) into 120-ml serum bottles in an anaerobic chamber (Coy Laboratory Products, Grass Lake, Mich.).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dissolved concentrations of Mn(II) and Fe(II) increased by a factor 20 within 7 days. Cooper et al (2000), who studied the formation of mineral phases during reduction, stated that microbial reduction of Fe(III) was inhibited when NO 3 − was present as an alternative electron acceptor. In this study, denitrification and Mn(IV) and Fe(III) reduction occurred simultaneously, and even simultaneous Fe(III) and SO 4 2− reduction was reported earlier (Postma and Jakobsen 1996;Vink 2002).…”
Section: Floodplain Soil Reductionmentioning
confidence: 99%
“…Postma and Jakobsen (1996) showed that the reduction of Mn, Fe, sulphate, and methanogenesis could be well explained by a partial equilibrium approach where the fermentive step (i.e., microbial reduction of organic matter) is rate limiting. Cooper et al (2000) reported on the impact of competition between nitrate and iron reduction on metal geochemistry, which may eventually block the processes that immobilize zinc during reduction.…”
Section: Introductionmentioning
confidence: 99%